2021
DOI: 10.1371/journal.pone.0249091
|View full text |Cite
|
Sign up to set email alerts
|

Lignosus rhinocerotis Cooke Ryvarden ameliorates airway inflammation, mucus hypersecretion and airway hyperresponsiveness in a murine model of asthma

Abstract: Lignosus rhinocerotis Cooke. (L. rhinocerotis) is a medicinal mushroom traditionally used in the treatment of asthma and several other diseases by the indigenous communities in Malaysia. In this study, the effects of L. rhinocerotis on allergic airway inflammation and hyperresponsiveness were investigated. L. rhinocerotis extract (LRE) was prepared by hot water extraction using soxhlet. Airway hyperresponsiveness (AHR) study was performed in house dust mite (HDM)-induced asthma in Balb/c mice while airway infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This may lead to AHR, bronchoconstriction and eventually lead to remodeling of the lung. 24) Airway remodeling is usually detrimental and can lead to continued airflow limitation, impaired lung function, and AHR. 25) The results of our study were consistent with those from previous studies on OVA-stimulated allergic asthma models.…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to AHR, bronchoconstriction and eventually lead to remodeling of the lung. 24) Airway remodeling is usually detrimental and can lead to continued airflow limitation, impaired lung function, and AHR. 25) The results of our study were consistent with those from previous studies on OVA-stimulated allergic asthma models.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, β-glucans have gained appeal for several emerging applications, including biopolymers 40 and biomedicines 41 . Notable potential therapeutic properties recently uncovered of mushroom-derived β-glucans include: (a) new or complementary immunotherapies against Coronavirus disease (SARS-CoV-2) 18 ; (b) new therapeutic agent for mitigating diseases associated with gastrointestinal mucosal damage, such as peptic ulcers and inflammatory bowel disease 42 ; (c) anticancer drugs for lung and breast cancer 43 ; and (d) asthmatic treatment 28 , 44 . However, there is a substantial gap in knowledge surrounding the toxicity (if any) of these mushroom-derived bioactive compounds, particularly on MB-EPS extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported on the efficacy of using EPS from medicinal mushrooms to ameliorate pro- and anti-inflammatory responses using ex vivo and in vivo infection models with therapeutic potential 16 , 18 , 27 . Aqueous extracts of L. rhinocerotis were reported to help reduce asthma-related variables in an asthma model 28 . In addition, a previous toxicity study indicated that feeding 1000 mg/kg of L. rhinocerus extract to rats had no detrimental consequences, hence it was considered safe 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors also reported a decrease in the percentage of CD4 + helper T cells in the lung-draining lymph nodes, including suppression of mucus secretion and leukocyte invasion in the lungs [108]. Johnathan et al (2021) in their study of oral consumption of LRE on airway inflammation using OVA-induced rat models observed significant elevation of CD4 + CD25 + Foxp3 + regulatory T cells in the BALF after treatment with LRE [109]. They also demonstrated down regulation of allergic/asthmatic-associated genes (IL-17A and ADAM33) following 7 days of L. rhinocerotis extract gavaging [109].…”
Section: Natural and Alternative Approachesmentioning
confidence: 97%
“…Johnathan et al (2021) in their study of oral consumption of LRE on airway inflammation using OVA-induced rat models observed significant elevation of CD4 + CD25 + Foxp3 + regulatory T cells in the BALF after treatment with LRE [109]. They also demonstrated down regulation of allergic/asthmatic-associated genes (IL-17A and ADAM33) following 7 days of L. rhinocerotis extract gavaging [109]. The preceding studies provided ample evidence on the in vivo effects of L. rhinocerotis in regulating the inflammatory mediators of allergy and asthma.…”
Section: Natural and Alternative Approachesmentioning
confidence: 99%